Case Report: A case of intrahepatic papillary neoplasm of the bile duct with invasive carcinoma in a young patient and review of the literature - Hu, Linhui; Wan, Hua; Hong, Yuan; Liang, Li; Wang, Yan (Frontiers in Oncology, 2025)
IntroductionIntrahepatic papillary neoplasm of the bile duct (IPNB) with invasive carcinoma is a rare cholangiocarcinoma with the most frequent site of origin being intrahepatic bile ducts. Given its rarity and non-specific clinical presentations, accurate diagnosis plagues clinicians to improve patient outcomes.Case presentationWe present a case of a 31-year-old male who initially exhibited fever. Routine ultrasonography and computed tomography (CT) revealed a large mass in the right liver lobe, suggesting a high likelihood of an infectious lesion. However, multidisciplinary discussion offered a variety of possible scenarios. The patient subsequently underwent an extended right hepatectomy (ERH), and histopathological examination suggested a intrahepatic IPNB with invasive adenocarcinoma.Clinical discussionThe diagnosis and management of IPNB remain challenging, particularly in patients who present with atypical clinical symptoms and lack significant abnormalities in laboratory tests. Early imaging plays a critical role in guiding the diagnostic process. However, comprehensive diagnostic speculations, clinical expertise, and even invasive detections are essential for establishing a definitive diagnosis and determining the appropriate treatment strategy. Given the potential to invasive carcinoma, early detection and resection are vital to improving prognosis.